HUBUNGAN KADAR PLUMBUM DARAH DENGAN ANEMIA PADA ANAK JALANAN DI DAERAH ISTIMEWA YOGYAKARTA - , JOSEPHINE DIONY NANDA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Lead intoxication is a major problem that mostly happened in developing country. High lead concentration in the air can cause increasing lead concentration inside people who mostly doing their activity in the road continuously. Concentration of lead above the normal range can lead to many clinical problems, one of them is anemia. Waifs and stray is one of vulnerable subjects to be exposed by lead in their daily life. Objective: The aim of this study is to know the relationship between lead concentration in the blood and anaemia. Subject and Method: The subjects are waifs and stray in Rumah Singgah Girlan Nusantara a number of 55 people. This study used cross sectional study design. Result: From 55 subjects, known that 36 people have blood-lead concentration <10 Î¼g/dl and 14 people have blood-lead concentration â¥10 Î¼g/dl inside their body. Using statistical test, known there is very weak correlation with positive sign, but not significantly different in statistic review (r=0,092